2014
DOI: 10.1063/1.4867388
|View full text |Cite
|
Sign up to set email alerts
|

Defect-mediated relaxation in the random tiling phase of a binary mixture: Birth, death and mobility of an atomic zipper

Abstract: This paper describes the mechanism of defect-mediated relaxation in a dodecagonal square-triangle random tiling phase exhibited by a simulated binary mixture of soft discs in 2D. We examine the internal transitions within the elementary mobile defect (christened the 'zipper') that allow it to move, as well as the mechanisms by which the zipper is created and annihilated. The structural relaxation of the random tiling phase is quantified and we show that this relaxation is well described by a model based on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Recent simulation studies [72] of the ST2 model of water [80] have shown that the FS crossover can be described in terms of the concentration of defects in the network, while similar results have been obtained for network forming colloids [81] and nanoparticles [82]. The structural relaxation of a two-dimensional random tiling model has also been described in terms of defect motion [83]. These studies suggest that understanding how defects effect structural relaxation may provide insight to the dynamics of amorphous systems.…”
Section: Discussionmentioning
confidence: 63%
“…Recent simulation studies [72] of the ST2 model of water [80] have shown that the FS crossover can be described in terms of the concentration of defects in the network, while similar results have been obtained for network forming colloids [81] and nanoparticles [82]. The structural relaxation of a two-dimensional random tiling model has also been described in terms of defect motion [83]. These studies suggest that understanding how defects effect structural relaxation may provide insight to the dynamics of amorphous systems.…”
Section: Discussionmentioning
confidence: 63%
“…the formation of cracks, which is in striking contrast to the behaviour of one-component crystals near melting [36]. Furthermore, the breakage of the thermal binary crystal resembles the plastic deformation of amorphous materials [50][51][52][53][54][55][56][57], where, due to the absence of distinct topological defects, plastic deformation is mediated by localized patterns of nonaffine motion [52,[58][59][60][61][62][63][64] and can be traced by the inherent stress signature and spatial correlation of plastic events [65][66][67] or contact force distributions [68]. Our results are verifiable in real-space experiments of superparamagnetic colloidal mixtures at a pending air-water interface in an external magnetic field [69][70][71][72][73], where the shear can be induced by an external laser field.…”
Section: Introductionmentioning
confidence: 99%